(untitled) (The Pakistan Development Review, 2025)
Over the last two decades, ‘accountability’ has become Pakistan’s most famous political slogan (Mehboob, 2022). Despite numerous reforms in the accountability system, Pakistan got the worst ranking in the region based on the Corruption Perception Index (CPI) published by Transparency International (TI) (TI, 2022). The CPI-based ranking shows that Pakistan ranked 140th out of 180 countries in 2021. Pakistan ranked well below the South Asian economies